Seleção de áreas potenciais para implantação da zona de processamento e exportação de Fernandópolis - SP utilizando geotecnologia - Moraes, Igor Amedi de [UNESP] (2011)
The implementation of an Export and Processing Zone (ZEPs) brings several benefits to the local, state and federal economy, but often, only socioeconomic factors are considered, apart from several other factors that should be analyzed, such as the environment. In this context of industrialization and the struggle for sustainable development, this work propose to incorporate the environmental variable in the decision process for establishing industrial areas, in particular, the ZPE in the city of Fernandópolis, São Paulo state, Brazil, by examining several physical and environmental factors such as slope intervals, geological features, pedological factors and land use. Developed using a multicriteria analysis, a model has been elaborated, where these factors have received a proportional value according with their importance, supported by a GIS tool (Geographical Information System) and remote sensing products, such as images from CBERS satellite and SRTM radar, showing the suited areas for industrial activities, considering environmental conditions. This model may assist to take better decision about the ZPE implementation area and to reduce the negative environmental impacts that would result of poorly planned locations